The Implementation of Sanctions as an Effort to Handle Covid-19 Pandemic in Medan City (Study on Covid-19 Handling Task Unit in Medan City) - Muhammad Din Alfajar; Eko Yudhistira; Fadhillah Fahmi Adriany (Budapest International Research and Critics University, 2022)
The government has established a health protocol policy through the Decree of the Minister of Health of the Republic of Indonesia Number HK.01.07/MENKES/382/2020 concerning Health Protocols for the Community in Public Places and Facilities in the Context of Prevention and Control of Corona Virus Disease 2019 (COVID-19). In supporting this policy, there are provisions of other laws and regulations that contain sanctions, both administrative sanctions and criminal sanctions. In theory, there are many views put forward by experts regarding the purpose of imposing criminal sanctions (sanctions). Based on existing criminal theories, criminal law enforcement policies will be analyzed in tackling the Covid-19 pandemic, especially in the city of Medan. This begins by identifying legal provisions regarding sanctions for violators of health protocols. Then analyze whether the legal provisions made for violators of the health protocol can achieve the expected sentencing goals. The research method used is normative legal-empirical law research (combined) using primary data and secondary data obtained through field research and library research. The field study was carried out at the Covid-19 Handling Task Force in Medan City. This study will explain the provisions of existing laws and regulations from the level of the Act to Regional Regulations that regulate sanctions for violators of health protocols.